Enhanced UVC Responsivity of Heteroepitaxial α-Ga2O3 Photodetector with Ultra-Thin HfO2 Interlayer - SiSung Yoon; SeungYoon Oh; GyuHyung Lee; YongKi Kim; SunJae Kim; Ji-Hyeon Park; MyungHun Shin; Dae-Woo Jeon; GeonWook Yoo (Micromachines)
In this study, the influence of HfO2 interlayer thickness on the performance of heteroepitaxial α-Ga2O3 layer-based metal–insulator–semiconductor–insulator–metal (MISIM) ultraviolet photodetectors is examined. A thin HfO2 interlayer enhances the interface quality and reduces the density of interface traps, thereby improving the performance of UVC photodetectors. The fabricated device with a 1 nm HfO2 interlayer exhibited a significantly reduced dark current and higher photocurrent than a conventional metal–semiconductor–metal (MSM). Specifically, the 1 nm HfO2 MISIM device demonstrated a photocurrent of 2.3 μA and a dark current of 6.61 pA at 20 V, whereas the MSM device exhibited a photocurrent of 1.1 μA and a dark current of 73.3 pA. Furthermore, the photodetector performance was comprehensively evaluated in terms of responsivity, response speed, and high-temperature operation. These results suggest that the proposed ultra-thin HfO2 interlayer is an effective strategy for enhancing the performance of α-Ga2O3-based UVC photodetectors by simultaneously suppressing dark currents and increasing photocurrents and ultimately demonstrate its potential for stable operation under extreme environmental conditions.